The effect of involving the Kuwaiti labor market in developing the Public Authority for Applied Education and Training (A proposal to develop the curricula of the Mechanical Business Department) - Al-Awadhi, Mohammad Ahmed Mohammad (Journal of Educational and Psychological Sciences, 2023)
Industrial life is rich in modern technology, which is always advanced. This development always puts the business owner in pursuit of it, in order to increase his material gains first and second for other considerations that differ from one place to another. And with the existence of bureaucratic procedures in the administrative systems, the training process within the training institutes has become not keeping pace with this development in the labor market. Labor market We have always suffered from this gap, and it grows with the passage of time, as the training process takes place completely isolated from the labor market. It is a system that focuses on involving the labor market and making it feed back into the development process alongside those in charge of the training operations. Thus, the impasse of the graduate’s misalignment with the labor market is overcome, and the labor market is made compatible with the outputs of the training process. In this system, the requirements of the labor market are crystallized in the form of competencies, and then Transforming these competencies into performance procedures that the trainee performs in front of a committee composed of industrialists and those in charge of the training process. So here we are in the process of working on the competencies of a graduate who is able to keep pace with modernity. What also distinguishes this system is its continuous updating, so it does not stop at a specific time, but rather constantly updates itself in accordance with what is new in the labor market.